2014
DOI: 10.1177/0162353214540826
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Success

Abstract: The underrepresentation of ethnic minority and economically disadvantaged students in gifted education must be understood in terms of broader school contexts and practices. This qualitative study investigated how teachers and schools contributed to the academic success of minority students of high potential from economically disadvantaged backgrounds. Researchers collected observation, interview, and documentary data for 2 years at each of three case study sites with a reputation of effectiveness in supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…Several scholars have suggested that access to appropriately challenging curricula contributes to high academic achievement. Yet, if children are required to score higher on standardized tests than is reasonable given their prior educational opportunities in order to receive gifted services they may fail be challenged by their schoolwork (Matthews & Foster, 2005;Reis, Hebert, Diaz, Maxfield, & Ratley, 1995;Tomlinson & Jarvis, 2014). Low educational attainment limits access to well-paying employment and thus the cycle of poverty is likely to repeat itself ( , Friedman, and Rockoff, 2011;Duncan & Magnuson, 2011;Entwisle & Alexander, 1999;Owens, 2010;Yalma & Tyner, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Several scholars have suggested that access to appropriately challenging curricula contributes to high academic achievement. Yet, if children are required to score higher on standardized tests than is reasonable given their prior educational opportunities in order to receive gifted services they may fail be challenged by their schoolwork (Matthews & Foster, 2005;Reis, Hebert, Diaz, Maxfield, & Ratley, 1995;Tomlinson & Jarvis, 2014). Low educational attainment limits access to well-paying employment and thus the cycle of poverty is likely to repeat itself ( , Friedman, and Rockoff, 2011;Duncan & Magnuson, 2011;Entwisle & Alexander, 1999;Owens, 2010;Yalma & Tyner, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding educators' perceptions of Students of Color and low socioeconomic status students' abilities in the elementary school setting is a topic that must be explored. There are significant differences in student outcomes that vary according to social class category (Nan & Hasan, 2010;Pringle, Lyons, & Booker, 2010;Tomlinson & Jarvis, 2014;Williams, 2011). Both working-class and Students of Color, particularly African Americans, are vulnerable to underachievement and low attainment in school (Dunne & Gazeley, 2008;Nan & Hasan, 2010).…”
Section: Teacher Beliefs About Students Of Color and Poor Studentsmentioning
confidence: 99%
“…Kingston (2011) views struggling students as either culturally deprived or lacking the innate ability for academic success. Investigation of the phenomenon through the cultural capital lens may account for the thought processes of Kingston and other educators, drawing possible conclusions for academic disparities from valued cultural capital through the White institutional hegemony (Tomlinson & Jarvis, 2014).…”
Section: Cultural Capital Theory Rationalementioning
confidence: 99%
See 2 more Smart Citations